2021
DOI: 10.1155/2021/9912743
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hepatitis B Carrier Status and Its Negative Association with Hypertensive Disorders in Pregnancy

Abstract: Background and Objectives. To evaluate whether a negative association between chronic hepatitis B carrier status and hypertensive disorders in pregnancy could continue to be demonstrated in an endemic area with a changing prevalence for chronic hepatitis B infection. Study Design. A retrospective cohort of all deliveries in a single centre over a period of 20 years in a population with high prevalence for chronic hepatitis B carrier status was studied. Main Outcome Measures. The primary outcome was the prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…However, only a small number of studies (n=13) were included for Hong Kong, with few data prior to 1993. Of note, a very recently published study that has been included in our meta-analysis reported an approximately 50% reduction (10.0% to 5.3%) in HBsAg prevalence in Hong Kong between 2000 and 2019, 37 suggesting that HBsAg, although still relatively high compared with other regions of China, is also decreasing in Hong Kong.…”
Section: Discussionmentioning
confidence: 74%
“…However, only a small number of studies (n=13) were included for Hong Kong, with few data prior to 1993. Of note, a very recently published study that has been included in our meta-analysis reported an approximately 50% reduction (10.0% to 5.3%) in HBsAg prevalence in Hong Kong between 2000 and 2019, 37 suggesting that HBsAg, although still relatively high compared with other regions of China, is also decreasing in Hong Kong.…”
Section: Discussionmentioning
confidence: 74%
“…However, other studies did not identify such an association or had contrasting results. 40 Patients with elevated ALT levels before treatment had a higher incidence of post‐partum hepatitis flare. 41 , 42 Our results found that HBsAg‐positive participants, particularly those who are HBeAg carriers, had significantly high ALT levels.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have shown that HBV infection does not affect the development of preeclampsia, 27,39 and our result is in accordance with this finding. However, other studies did not identify such an association or had contrasting results 40 . Patients with elevated ALT levels before treatment had a higher incidence of post‐partum hepatitis flare 41,42 .…”
Section: Discussionmentioning
confidence: 99%
“…It suggests that the efforts to prevent and control hepatitis B have been effective. In Hong Kong, the seroprevalence of hepatitis B surface antigen (HBsAg) has declined in several populations with no obvious HBV risk, such as new blood donors and pregnant women [ 24 ]. Hong Kong has transitioned from a high-intermediate to an intermediate-low hepatitis B endemicity over the last few decades.…”
Section: Discussionmentioning
confidence: 99%